(untitled) (Research, Society and Development, 2020)
Introduction: Parkinson’s disease (PD) is known for its debilitating motor symptoms and the dependence that its progression causes. Although classic, this condition still does not have its causal factors fully elucidated and, therefore, the prediction sometimes becomes ineffective. In the search for a better understanding of the disease, researchers found an intimate relationship between their symptoms and populations that had contact with the pesticide rotenone, widely used in agricultural processes and that can be an auxiliary factor in the development of the disease in the agricultural population. Objective: To elucidate, based on the literature, the interrelation of Parkinson’s Disease with rotenone. Methodology: Integrative literature review that used the descriptors: “Parkinson Disease”, “Rotenone”, “Synucleins”, “Gastrointestinal Tract”, “Vagus Nerve” and “Microbiota” in the databases: PubMed, ScienceDirect, SCIELO, and BVS where 13 documents were selected for analysis that elucidated in their text the relationship between the disease and the substance studied. Results: The works portray an intimate relationship between exposure to rotenone and non-motor symptoms of Parkinson’s disease. Also, these symptoms mainly affect signs in the gastrointestinal tract, which sometimes can help in the prediction of the disease long before the manifestation of classic symptoms. Final Considerations: Rotenone has a well-elucidated relationship in the development of Parkinson’s disease, besides, this relationship allows a better understanding of the connection between the brain and the gastrointestinal tract through the vagus nerve. Thus, such findings can serve as a basis for a better understanding and prevention of the diagnosis and treatment of PD.